Preparation and characterization of a new liposomal paclitaxel formulation - Koudelka, Štěpán; Turánek, Jaroslav (Univerzita Pardubice, 2008)
Stable lyophilised liposomal preparation of paclitaxel (7 mol%) encapsulated in the liposomes composed of SOPC/POPG/MOPC (60:20:20 molar ratio) and doped with vitamin E (5 mol%) was prepared by various procedures: hydration of lipid film, the proliposome-liposome method and lyophilisation from 2-methylbutan-2-ol. Extrusion through 0.2 um polycarbonate membranes was applied as a secondary processing technique to reduce the size distribution of liposomes to about 180 - 190 nm (PDI 0.1). A negative charge (zeta-potential of -30mV in saline phosphate buffer) was sufficient to prevent flocculation and fusion of liposomes in suspension. An isocratic reverse-phase high performance liquid chromatography (HPLC) method with ultraviolet (UV) detection was used for determination of paclitaxel in liposomal preparations. The value of paclitaxel encapsulation efficiency (EEPTX) was determined to be approximately 95 %. Mannitol, lactose, sucrose and trehalose were tested as cryoprotective agents. Except for mannitol, all the tested saccharides were equally cryoprotective at lipid:saccharide molar ratios of 1:5 and 1:10.